Source book for linguistics - Cowan, William (J. Benjamins, 1998)
This is a revised and expanded edition of Cowan and Rakušan's Source Book for Linguistics. In addition to the chapters on Phonetics, Phonology, Phonological Alternations, Morphology, Syntax, Sound Change and Historical Reconstruction, there are two new chapters: one on Semantics and one on Grammatical and Lexical Change. In addition, an index of the 93 languages and dialects represented in the book has been added, as well as a revised bibliography. The solutions to the exercises have also been revised and expanded. The number of exercises has been increased from 333 to 472. New exercises have.